Essay Writing Through Retrospective Thinking: Multiphotography as a Metaphor of the Liaison between Essay, Memory and Fiction in Paul Auster’s “Portrait of an Invisible Man” - Aguirre, Eduardo (2019)
The purpose of this article is to establish a certain type of relationship between essay, memory and fiction. We will demonstrate that this particular combination doesn´t happen exclusively because prose is fictionalized since the writer’s memory is suspicious and unreliable (common place of criticism), that is to say that whoever engages in essayistic writing from memory tends to mystify its object of study, multiplying it as who puts two mirrors face to face, presenting the image multiplied under the appearance of personal experience. In order to do this, first we will inspect the proximity between essay and memoir’s; afterwards, we will exhibit the way in which essay writing is activated through diffuse and reconstructed memory. In the end, as evidence to our premise, we will attest how this is done in “Portrait of an Invisible Man” by American writer Paul Auster.